ISLAM DAN PERADABAN - Mukhamad Anieg (Kopertais Wilayah X Jawa Tengah, 2015)
Abstract! e word Civilization is often given the same meaning with culture. But there is a di erence in meaning between the two terms. The term Civilization to civilization and Culture for culture. Similarly differentiated between in Arabic word Tsaqafah (culture), said Hadharah (progress), and of the Tamaddun(civilization). Al-kala’i argues that culture in the Arabic language means al-tsaqofah.Initially, i.e. from the time of Rosululloh until the 12th century ad this civilization has managed successfully so that it can give birth to world-class historians so that from here can also give birth to community organizations,the economic centre of the region, language, education, religious belief and science, all of which were based on the religion of islam. Already quite a lot of Americans, Europeans and others converted to Islam. However, unfortunately the addition of Muslims is not coupled the readiness concept in Islamiccivilization progress. at this time the quantity of people the most is the religion of Islam which reached 1.4 billion people. But it is not the completion of the Muslims in the face of the progress of civilization.Finally the triumph of Islam was down. ! erefore, we must build the Islamic Civilization.Keyword: Civilization, religious, community.